A Redox-active Mn Porphyrin, MnTnBuOE-2-PyP5+, Synergizes with Carboplatin in Treatment of Chemoresistant Ovarian Cell Line. (9th May 2022) - Chaiswing, Luksana; Yarana, Chontida; St. Clair, William; Tovmasyan, Artak; Batinic-Haberle, Ines; Spasojevic, Ivan; St. Clair, Daret
Abstract : We have employed a redox-active MnP (MnTnBuOE-2-PyP 5+, Mn(III) meso-tetrakis (N-n-butoxyethylpyridinium-2-yl) porphyrin) frequently identified as superoxide dismutase mimic or BMX-001, to explore the redox status of normal ovarian cell in relation to two ovarian cancer cell lines: OV90 human serous ovarian cancer cell and chemotherapy-resistant OV90 cell (OVCD). We identified that OVCD cells are under oxidative stress due to high hydrogen peroxide (H2 O2 ) levels and low glutathione peroxidase and thioredoxin 1. Furthermore, OVCD cells have increased glycolysis activity and mitochondrial respiration when compared to immortalized ovarian cells (hTER7) and parental cancer cells (OV90). Our goal was to study how ovarian cell growth depends upon the redox state of the cell; hence, we used MnP (BMX-001), a redox-active MnSOD mimetic, as a molecular tool to alter ovarian cancer redox state. Interestingly, OVCD cells preferentially uptake MnP relative to OV90 cells which led to increased inhibition of cell growth, glycolytic activity, OXPHOS, and ATP, in OVCD cells. These effects were further increased when MnP was combined with carboplatin. The effects were discussed with regard to the elevation in H2 O2 levels, increased oxidative stress, and reduced Nrf2 levels and its downstream targets when cells were exposed to either MnP or MnP/carboplatin. It is significant to emphasize that MnP protects normal ovarian cell line, hTER7, against carboplatin toxicity. Our data demonstrate that the addition of MnP-based redox-active drugs may be used (via increasing excessively the oxidative stress of serous ovarian cancer cells) to improve cancer patients' chemotherapy outcomes, which develop resistance to platinum-based drugs.